Evaluasi Penggunaan Material Bekisting Kayu pada Proyek Pembangunan Mall Pelayanan Publik Kabupaten Muaro Jambi - Setiawan, Adit; Handayani, Elvira; Dony, Wari; Dwiretnani, Annisaa (Jurnal Talenta Sipil, 2025)
This formwork plays a role in printing concrete for structural work such as foundations, sloofs, columns, beams, and floor slabs. This type of formwork is the main material used wood and plywood. Repeated use of materials can affect cost efficiency, but with good results. The location of this research was carried out in a public service mall construction project with a building area of + 462 m2 which was built on the Bukit Cinto Kenangan Sengeti office complex road, Muaro Jambi Regency. The method used is to collect the necessary research data, namely the Cost Budget Plan (RAB), Work Unit Price Analysis (AHSP), Plan Drawings and material purchase reports. This study aims to compare costs between AHSP, RAB and material purchase reports needed for wooden and plywood formwork materials, namely the cost of AHSP of IDR 75,591,800 while the RAB is IDR 79,097,080 and the material purchase report is IDR 58,744,000. This study also calculates the volume requirements for repeated use of formwork (two times use) in column formwork work, the material of class III wood formwork is 5.373 while class II wood is 2.01 m3 and plywood is 47 sheets with 269 pieces of galam wood. In beam formwork work, the material of class III wood formwork is 5.29 m3 while class II wood is 2.38 m3 and plywood is 47 sheets with 265 pieces of galam wood.